Removal of 4-Chlorophenol Using Graphene, Graphene Oxide, and A-Doped Graphene (a = N, B): A Computational Study - Cortes-Arriagada, D; Wrighton-Araneda, K (2013)
Density functional theory (including van der Waals correction with the PBE-D functional) is applied to the study of 4-chlorophenol (4-CP) adsorption on graphene oxide (GO), A-doped graphene (A = N, B), and pristine graphene and test their possible application for 4-CP removal. Results show that on GO adsorption is improved by the hydrogen bond interactions between the adsorbents and 4-CP, suggesting that functionalized graphene is a preferable alternative than pristine graphene for 4-CP removal. In addition, the stability of hydrogen bonds is confirmed by molecular dynamics calculations using the PM6 potential. Without hydrogen bonds, A-doped graphene models show a comparable performance for 4-CP removal than pristine graphene. Finally, even in a solvent medium, 4-CP adsorption is strong. Copyright © 2013 Wiley Periodicals, Inc.